Uterine Non-Hodgkin Lymphoma: A Rare Gynaecological Presentation - F. D. Haleemah Olalere; Abraham F. Adeyeye; Taiwo O. Kuye; Adeyemi F. Tijani; Fatimah A. Rabiu; Abiodun R. Bamiro; Akinsegun A. Akinbami (Recent Developments in Medicine and Medical Research Vol. 10, 2021)
Primary extranodal non-Hodgkin lymphomas of the genital tract are rare, and engagement of the uterine corpus is not only extremely rare but also lacks pathognomonic signs and symptoms, resulting in delayed diagnosis and treatment. This prompted the publication of this case report of a multiparous woman who presented with recurrent vaginal bleeding and progressive abdominal swelling that was initially suspected to be uterine sarcoma. She had a surgical operation twice, which was initially inoperable in a secondary facility, and subsequently had a total abdominal hysterectomy and bilateral salpingo-oophorectomy and omentectomy in a private facility by a gynaecologist and general surgeon. Specimens removed were sent for histopathological analysis and the diagnosis of high-grade large B-cell type non-Hodgkin lymphoma of the uterus was made. However, her condition deteriorated further, culminating in her demise on account of multiple organ failures before the commencement of chemotherapy. This report also emphasized the difficulties in diagnosis and management in a resource-limited setting where advanced diagnostic aids are not readily available. Although uterine non-Hodgkin lymphoma is uncommon, it should be considered in any patient who has an abdominal/pelvic mass and/or abnormal vaginal bleeding.